Agent-based financial markets and New Keynesian macroeconomics: A synthesis - Matthias Lengnick; Hans-Werner Wohltmann (Kiel University, Department of Economics, 2010)
We combine a simple agent-based model of financial markets with a standard New Keynesian macroeconomic model via two straightforward channels. The result is a macroeconomic model that allows for the endogenous development of stock price bubbles. Even with such a simplistic comprehensive model, we can show that the behavioral foundations of the stock market exert important influence on the macroeconomy, e.g. they change the impulse-response functions of macroeconomic variables significantly. We also analyze financial market transaction taxes as well as asset price bubble deflating monetary policy, and find that both can be used to reduce volatility and distortion of the macroeconomic aggregates.
Keywords: E0; E52; G12; G18; 330; agent-based financial markets; New Keynesian macroeconomics; stock market; transaction tax; Taylor rule; Börsenkurs; Bubbles; Finanzmarkt; Agent-based Model; Ungleichgewichtstheorie; Börsenumsatzsteuer; Taylor-Regel; Wirkungsanalyse; Theorie